Zinc fractionation of tropical paddy soils and their relationships with selected soil properties - Soltani, Shahram Mahmoud; Musa, Mohamed Hanafi; Abd. Wahid, Samsuri; Syed Muhammad, Sharifah Kharidah (Taylor & Francis, 2015)
Knowledge of zinc (Zn) distribution among various fractions will help to predict the potential of the soil to supply sufficient Zn for crop production. The present study was done to investigate Zn fractions, Zn availability factor (AF) and their relationship with soil properties of Zn-deficient tropical paddy soils. The samples of two soil orders (six soil series) were sequentially extracted with chemical extractants in two different growth stages of rice (maximum tillering and flowering stages). The proportion of Zn fractions extracted at the maximum tillering stage followed the order, water soluble plus exchangeable (WE) < crystalline sesquioxide (Cry) < manganese oxide (MN) < organically bound (Org) < amorphous sesquioxide (Amor) < residual Zn (Res), whereas the order at the flowering stage was as follows: WE < Mn < Cry < Org < Amor < Res. Cation exchange capacity (CEC), clay content and organic carbon (OC) were the most important factors controlling the distribution of Zn in soils. The AF was low in Tok Young (1.79%), high in Telemong (17%) and medium in the rest of soil series (around 8%). A stepwise multiple linear regression and principal component analyses showed that OC, clay content and CEC were the main variables that explained the predictability of Zn fractions. The result of the length of submerging showed that the WE, Org and Cry concentrations decreased, while Amor, MN, and the sum of all Zn fractions increased with increase in the flooding period. The extractability and solid-phase fractionation of Zn in two different times of soil sampling showed the importance of timing of Zn fertilizer application and flooding or pre-flooding in Zn availability.